GIFTED EDUCATION PROFESSIONAL DEVELOPMENT - Creecy, Lisa E. (Acta Scientiae et Intellectus, 2024)
This paper reviews the current research regarding professional development in general education and gifted education. It provides various models of professional development for general education that can easily be transferred to gifted education and the gifted education professional.